Horizontal transmission of hepatitis B virus amoung household contacts of the asypmtomatic paediatric patients at Cancer Institute, Maharagama - Sylva, K.K.S.D (My University, 2007)
It is a well-known fact that a higher prevalence of hepatitis B infection is seen among cancer patients under going multiple invasive investigations and therapeutic procedures. Once infected there is a higher chance of them going in to chronicity as their immune systems are compromised. This is even more so when the index case is a child due to the immaturity of the immune system. Hence, horizontal transmission of the virus is easier to occur in such an instance. It had been noticed by the clinicians of the Cancer Hospital, Maharagama that there had been an increase of hepatitis B infection among patients. Therefore, it was important to identify the asymptomatic HBsAg carrier patients and the extent of horizontal transmission, in order to prevent further spread of hepatitis B infection in the household contacts of carrier patients.To determine the prevalence of HBV markers in paediatric cancer patients at Cancer Institute, Maharagama.To determine the prevalence o HBV markers in household contacts of HBsAg The study was carried out at Cancer Institute, Maharagama (CIM) from July to October 2003. 103 blood samples were collected from asymptomatic paediatric patients who were chosen - randomly from wards and clinics and the sera were tested for HBsAg, anti-HBs, anti-HBc (total) using reverse passive haemeagglutination, - passive haeme- agglutination anQiEtISA respectively. 110 household contacts of the 34 patients who were positive for HBsAg were identified and their sera were tested for the same hepatitis B viral markers using the same tests. Doubtful results were retested with the same test. The prevalence of hepatitis B viral markers in asypmtomatic paediatric patients at CIM is as follows, HBsAg-33 percent , anti-HBs 5.8 percent , antiHBc 41.7 percent . The prevalence of hepatitis B viral markers in the household contacts of the HBsAg positive patients is as follows, HBsAg 2.73 percent , anti-HBs 33.6 percent , anti-HBc 52.7 percent According to the results obtained, hepatitis B sero-prevalence was found to be higher in paediatric patient population of CIM than that of the normal population in Sri Lanka. Most of the patients who had acquired the infection were asymptomatic posing a higher risk of transmission. Majority (79 percent) of the infected patients developed carrier state due to impaired immunity. There was a higher prevalence of HBV infection among household contacis of HBsAg carriers. Most (43 percent ) of them were siblings of the index case. Development of persistent infection in this group was comparable to that of the normal population. on a patient with past three abdominal delivaries; Post partum haemorrhage managed with s come, including preinstall morbidity and mortality. Of the goals of ante natal care, this is one of the most important continuum to remain. Measurement of the symphysio fundal height (SFH), the distance from the upper level of the symphysis pubis to the highest point of the uterine fundus, has traditionally been advocated, and is commonly used in ante natal clinics (ANC) in Sri Lanka as a screening tool. The chart currently used in Lankan ANC is provided by the Family Health Bureau (FHB) and it is included in the mother's record